Effectiveness of the Overall Monetary Policy 2082/083 in Promoting Credit Growth - Ghimire, Shankar (Jana Adarsha Research Journal, 2026)
This study provides an analytical review of Nepal Rastra Bank’s Monetary Policy for Fiscal Year 2082/83 (2025/26), with a particular focus on credit expansion and the role of quarterly policy reviews in policy adjustment. The research examines the background and objectives of monetary policy in Nepal, key policy instruments adopted during the fiscal year, and trends in private sector credit growth. Using secondary data from Nepal Rastra Bank publications, monetary policy statements, quarterly reviews, and macroeconomic indicators, the study evaluates the effectiveness of monetary policy measures in stimulating credit flow and supporting economic recovery. The analysis shows that although the monetary policy adopted an accommodative stance and ensured adequate liquidity in the banking system, credit growth remained moderate, especially during the early months of the fiscal year. The study further finds that weak private sector demand, risk-averse lending behavior of banks, slow monetary policy transmission, and structural constraints in productive sectors significantly limited the effectiveness of credit expansion measures. While the quarterly review played a supportive role in stabilizing liquidity conditions, guiding interest rates, and reinforcing policy credibility, its impact on accelerating credit growth was constrained by broader economic uncertainty and confidence-related issues. The study concludes that effective credit-led economic growth in Nepal requires not only accommodative monetary policy but also stronger monetary–fiscal coordination, targeted sectoral incentives, improved risk-sharing mechanisms, and structural reforms to enhance policy transmission and private sector confidence.